Comparison of Effectiveness of Clove Flower, Cinnamon Bark, and Star Anise Extract on the Growth of Escherichia coli Bacteria - Marpaung, Joy Mart; Panjaitan, Ivonne M. S.; Tobing, Joshua H. L. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Bacterial infections produce diseases such as Escherichia coli diarrhea, which is a big issue in developing countries. Clove flower (Syzygium aromaticum), Cinnamon bark (Cinnamomum verum), and Star anise (Illicium verum) contain active ingredients such as alkaloids, saponins, flavonoids, polyphenols, tannins, glycosides, and volatile oils which have potential as antibacterial. This study aims to analyze the difference in the inhibition zone of the extracts of the three plants extracted with 96% ethanol solvent against Escherichia coli using the disc diffusion method with extract concentrations of 15%, 20%, and 25%, and compare them with thiamphenicol as a positive control with the same concentration. The results show that the extracts have antibacterial activity that increases with the increase in concentration, where 25% concentration give the largest zone of inhibition. The clove extract has the highest inhibition, followed by cinnamon and star anise, although thiamphenicol remained the most effective. These findings confirm the significant antibacterial potential of all three extracts with α = 0,000.